Análise temporal do uso do solo e comparação entre os índices de vegetação ndvi e savi no município de Santa Cruz do Rio Pardo - SP usando imagens landsat-5 - Demarchi, Julio Cesar [UNESP]; Piroli, Edson Luís [UNESP]; Zimback, Célia Regina Lopes [UNESP] (My University, 2011)
This work aims to analyze the land use evolution in the city of Santa Cruz do Rio Pardo - SP through supervised classification of Landsat-5 TM satellite images according to the maximum likelihood (Maxlike), as well as verifying the mapping accuracy through Kappa index, comparing NDVI and SAVI vegetation indexes in different adjustment factors for the canopy substrate and determining the vegetal coverage percentage in all methods used on 2007, May 26 th; 2009, January 7 th and 2009, April 29 th. The Maxlike classification showed several spatial changes in land use over the study period. The most appropriated vegetation indexes were NDVI and SAVI - 0,25 factor, which showed similar values of vegetal coverage percentage, but discrepant from the inferred value for Maxlike classification.
Temporal analysis of the land use and comparison between ndvi and savi indexes in the city of Santa Cruz do Rio Pardo - SP using landsat-5 images
Keywords: Images classification; Land use mapping; Vegetation indexes; accuracy assessment; canopy; image classification; land use change; Landsat thematic mapper; landscape evolution; NDVI; temporal analysis; vegetation mapping; Brazil; Santa Cruz do Rio Pardo; Sao Paulo [Brazil]